KOMPETENSI WALI KELAS DALAM MEWUJUDKAN PRESTASI BELAJAR DI SEKOLAH MENENGAH ISLAM TERPADU - Abdillah, Ibnu Farhan; Sahraini, Sahraini; Masruddin, Masruddin; Kaharuddin, Kaharuddin; Mustaring, Dodi Ilham (Kelola: Journal of Islamic Education Management, 2023)
This study aims to (1) to determine the competence of homeroom teachers at SMPIT Insan Madani Palopo, (2) to find out what factors affect the competence of homeroom teachers at SMPIT Insan Madani Palopo. This research is qualitative descriptive research. The data collection techniques used are interviews, observations and document studies. The data analysis techniques used are reduction data, percentage data and conclusions. The results showed that the competence of homeroom teachers in improving student achievement at SMP Islam Terpadu Insan Madani Kota Palopo consists of: (1) Communication Skills, (2) Class Management, (3) Problem Solving. Factors that affect homeroom competence consist of internal factors and external factors. Internal factors are factors that originate from within a homeroom teacher such as personality and dedication and discipline in carrying out their profession as educators. Then external factors are factors that come from outside such as professional development, welfare and background or level of education taken